RISKS FOR PERIPHERAL ARTERIAL DISEASE IN THE ELDERLY WITH TYPE 2 DIABETES MELLITUS : Their Correlation with High Sensitivity C-reactive Protein and Ankle-Brachial Index - Ayu Tuty Kuswardhani, Raden; Wita, Wayan; Bakta, Made; Santosa, Anwar (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 3, No. 2 Juli 2009)
The Indonesian elderly population has been projected to increase up to about four-fold inthree decades (1990-2020). As a consequence of this population trend, the increased prevalence ofdegenerative diseases would be inevitable; this would include the prevalence of peripheral arterialdisease.This study aims to identify the correlation of diverse risk factors, either traditional or nontraditional,with the ankle-brachial index scores, and the correlation of novel non-traditional riskfactor, e.i. high sensitive C-reactive protein with the prevalence of perioheral arterial disease in theelderly, age 60-80 years old, with type 2 diabetes mellitus.Among the 146 elderly patients with type 2 diabetes mellitus, and based on measurement ofthe ABI score, approximately 30.9% of them had PAD. Some traditional and non-traditional riskfactors having a significant correlation with the ankle-brachial index score, were age (r = -0.396, p <0.001 for right ABI; r = -0.509, p < 0.001 for left ABI), supine systolic blood pressure (r= -0.268, p =0.012 for right ABI; r = -0.267, p = 0.013 for left ABI), 2-hour post-prandial blood glucose (r= -0.252, p = 0.018 for right ABI), and hsCRP (r = -0.280, p = 0.011 for right ABI; r = -0.402, p <0.001 for left ABI); whereas other risk factors like obesity based on waist circumference and BMI,non-supine systolic blood pressure, fasting blood glucose, HbA1C, duration of diabetes, plasma lipidsdid not show statistically significant different odd ratios. After linear regression test for risk factorshaving significant correlations with ABI, age and hsCRP were found to influence the ABI scores.Based on a case-control study, risk factors which, to some extent, had statistically significant valuesas risk factors, include older age (? 70 years old; OR = 7.737 [CI = 2.515-23.805]; p < 0.001),relatively high supine diastolic blood pressure (? 90 mmHg; OR = 6.882 [CI = 0.789-60.060]; p =0.048), and high concentration of hsCRP (> 3 mg/L; OR = 4.420 [CI = 1.287-15.181]; p = 0.013).Among these statistically significant risk factors, after logistic regression test analysis, only the age ofthe patient appeared to have significant influence on the prevalence of PAD.In conclusion, this study demonstrates a negative correlation between hsCRP and ABI score;and high levels of hsCRP appeared to be a risk factor for PAD. The age of the patient, however,appeared to be the strongest risk factor for PAD.
Keywords: Peripheral arterial disease, risk facors, elderly patient, type 2 diabetes mellitus, highsensitivity C-reactive protein, ankle-brachial index.